Analisis Resepsi terhadap Feminisme dalam Film Birds of Prey - Eryca Septiya Ningrum; Ineza Vedya Prishanti; Anjani Syafitri Ditasyah; Ifda Faidah Amura (CV. Syntax Corporation Indonesia, 2021)
Feminism is a movement to fight for gender equality between men and women. Many efforts have been made to support feminism, one of which is by using films. Film is a mass media that is persuasive enough to sedate the audience. Apart from being entertaining, films are also realistic media in depicting social, political economy and other problems. This study aims to determine the audience position from the three positions of readers stated by Stuart Hall through the film